2023
DOI: 10.1177/20552076221144181
|View full text |Cite
|
Sign up to set email alerts
|

Developing and testing an integrated patient mHealth and provider dashboard application system for type 2 diabetes management among Medicaid-enrolled pregnant individuals based on a user-centered approach: Mixed-methods study

Abstract: Background A tailored and integrated technology solution (patient mHealth application and provider dashboard) can provide a 360° view of Medicaid-enrolled patients with type 2 diabetes (T2D) during pregnancy that could improve health outcomes and address health inequities. Objectives To develop a set of user specifications for the mHealth and dashboard applications, develop prototypes based on user needs, and collect initial impressions of the prototypes to subsequently develop refined tools that are ready for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Prior investigations have also revealed that engaging in co-creation with the targeted end-users can significantly enhance the adoption of such a novel smartphone application. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have also revealed that engaging in co-creation with the targeted end-users can significantly enhance the adoption of such a novel smartphone application. 42 , 43 …”
Section: Discussionmentioning
confidence: 99%
“…Medicaid-insured pregnant individuals with T2D and their healthcare providers, including both physicians and nurses, clinical social workers and CHWs, have collaboratively worked with the study team in designing the mHealth app and dashboard interface by providing feedback about the intervention prototype via structured interviews over multiple iterations. 31 Additional testing of the integrated system and tools (ie, patient mHealth app and provider dashboard) to address usability and patient/provider centeredness will be conducted prior to the randomised controlled trial (RCT).…”
Section: Methods and Analysismentioning
confidence: 99%
“…Electronic data linked to patients’ mHealth apps can allow the care team to actively engage with patients in their care and help them to achieve treatment goals. 31 32 In addition, continuous glucose monitoring (CGM) is a personal mobile technology that allows identification of precise, individualised patterns of dysglycaemia. 33 CGM has been shown to improve glycaemic control and decrease the risk of adverse pregnancy outcomes for individuals with type 1 diabetes, 34 but its impact among pregnant individuals with T2D remains largely unstudied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and evaluating health literacy in mHealth (8). It is long known that health literacy is related to health outcomes (4,5). Other scoping reviews have indicated health literacy problems in specific areas such as genomic health information (9).…”
Section: Gap To Be Addressed For Mhealth Applicationsmentioning
confidence: 99%